Detecção do rearranjo da prpoteína BCL2/JH em carcinomas epidermóides de boca e faringe - Montovani, Jair Cortez [UNESP]; Sales, Magaly Machado; Pardini, Maria Inês de Moura Campos [UNESP] (Thieme, 2010)
The BCL2 protein found in the internal mothocondrial membrana regulates the apoptosis preventing the programmed cell death. The translocation (14:18), detected in 70 to 85% of the follicular lymphoma, lead the super expression of BCL2 protein, by juxtaposition of BCL2 gene to the JH segment of the immunoglobulins' heavy chain gene. However, the found of the BCL2 expression in head and neck carcinoma are contradictious. OBJECTIVE: To investigate the presence of the translocation (14:18) of the BCL2 gene in head and neck carcinoma. METHOD: Sixteen DNA samplers were examinated being 13 of squamous cells carcinoma (SCC) and 3 of epidermoid (CE), y means of chain reaction of the polymerase (PCR). RESULTS: The BCL2/JH rearrangement in 2 (15%) of the CCE 13 cases and in none of the 3 cases of CE. The average of the frequency of molecules with rearrangement was 46,44x107. Was not observed association between the rearrangement presence and the exhibition to tobacco and alcohol (p=0, 6545). CONCLUSION: Different from the results found in follicular lymphoma, the presence of the translocation (14; 18) in head and neck carcinomas is not common and, when it occurs, it can be an occasional mutation not associated to exhibition to the tobacco and alcohol.

A proteína BCL2 encontrada na membrana mitocondrial interna, regula a apoptose inibindo a morte celular programada. A translocação (14;18), detectada em 70 a 85% dos linfomas foliculares, leva a superexpressão da proteína BCL2, pela justaposição do gene BCL2 ao segmento JH do gene da cadeia pesada da imunoglobulina. Porém, os achados da expressão da BCL2 em carcinoma de cabeça e pescoço são contraditórios. OBJETIVO: Investigar a presença da translocação (14;18) do gene BCL2 em carcinomas de cabeça e pescoço. MÉTODO: Foram examinadas 16 amostras de DNA, sendo 13 de carcinomas de células escamosas (CCE) e 3 de epidermoide (CE), por meio da reação em cadeia da polimerase (PCR). RESULTADOS: O rearranjo BCL2/JH foi encontrado em 2 (15%) dos 13 casos de CCE e em nenhum dos 3 casos de CE. A média de frequência de moléculas com rearranjo foi de 46,44 x 107. Não foi observada associação entre a presença de rearranjo e a exposição ao tabaco e álcool (p=0,6545). CONCLUSÃO: Diferente dos resultados encontrados em linfomas foliculares a presença da translocação (14;18) em carcinomas de cabeça e pescoço não é comum e, quando ocorre, pode ser uma mutação ocasional não associada a exposição ao tabaco e álcool.
Detection of protein BCL2/JH rearrangement in epidermoid carcinomas of mouth and pharynx
Keywords: Genetics translocation; Molecular biology; Buccal neoplasia; Pharyngal neoplasia; Translocação genética; Biologia molecular; Neoplasias bucais; Neoplasias faríngeas